Urogenital anomalies in children with anorectal malformations: a single institution observational study - Wondemagegnehu, Belachew Dejene; Asfaw, Solomon Wubetu (Frontiers in Surgery, 2025)
IntroductionAnorectal malformations (ARM) consist of a range of anomalies that occur in approximately 3.5 in 10,000 live births. Though variable, about half of these patients present with an associated genitourinary abnormality. Considering this high prevalence, this study aimed to assess the specific occurrence of urogenital anomalies in patients with anorectal malformations.MethodsAn institution-based observational study was conducted on 156 patients with anorectal malformation, all of whom were screened for urogenital anomalies. Data were collected using a pre-structured questionnaire and analyzed using SPSS (IBM) Version 26 software. Relevant statistical analysis was performed, and the results are presented in tables.Results and discussionOf the 156 patients with ARM studied for associated urogenital anomalies, 91 (58.3%) were females with a male-to-female ratio of 0.7:1 and a median age of 12 months (IQR = 1–24). Forty-six of them (29.5%) had urogenital anomalies, of whom 22 (14.1%) had isolated urologic anomalies and 20 (12.8%) had both urologic and genital anomalies. Renal anomalies were found in 34 (21.8%) patients. The association between gender and genital anomalies was significant, χ2 (1), N = 156 = 4.09, p = 0.04. The type of ARM has a highly significant association with genital anomalies χ2 (11), N = 156 = 21.95, p = 0.009. Males were less likely to exhibit urogenital anomalies [OR = 0.386, 95% CI (0.15–0.995), p = 0.048]. Children with complex ARM have 3.4 times genital and 2.3 times urinary anomalies than less complex forms. In summary, urogenital anomalies are the most common anomalies occurring in association with anorectal malformation. Genital anomalies have an association with gender with more occurrence in females. Children with complex anorectal malformations have a higher chance of urogenital anomalies.